Safety assessment of temozolomidee: real-world adverse event analysis from the FAERS database - Liu, Yu; Ma, Lan; Fu, Xiaojia; Zhang, Yi; Zheng, Jinyu; Chen, Zhongjun (Frontiers in Pharmacology, 2025)
BackgroundTemozolomidee (TMZ) is an alkylating antitumor drug used in the treatment of glioblastoma and anaplastic astrocytoma. It is often combined with radiotherapy and has cytotoxic effects on tumor cells. Although temozolomidee has a certain efficacy in the treatment of brain malignancies, its numerous adverse effects (AEs) suggest that its safety needs to be thoroughly evaluated.MethodsBased on data from the FDA Adverse Event Reporting System (FAERS) database, a retrospective pharmacovigilance study was conducted to evaluate temozolomide-related adverse events. Methods for identifying temozolomide-related AEs signals include taking a case/non-case approach. Specific detection algorithms also include report Odds ratio (ROR), Proportional Report ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item Gamma-Poisson constrictor (MGPS).ResultsAmong 48,766,547 FAERS reports, 13,608 TMZ-related AEs were identified. Males (53.66%) and patients aged ≥45 years predominated. The most frequent outcomes were hospitalization (35.76%), death (22.79%), and serious AEs (34.24%). Hematologic toxicities dominated, with “blood and lymphatic system disorders” showing the strongest signal (ROR 5.94, 95% CI: 5.73–6.15; PRR 5.48). Notable PTs included *petechiae* (ROR 9.87), *hemiparesis* (ROR 9.36), and *platelet count decreased* (ROR 8.61). Unexpected AEs, such as *pulmonary embolism* (ROR 4.96) and *Pneumocystis jirovecii pneumonia* (ROR 7.09), were identified. Renal/metabolic disorders (e.g., hypernatremia) and neurotoxic events (e.g., seizures, ROR 6.19) also demonstrated significant signals.ConclusionThis large-scale analysis highlights TMZ’s association with severe hematologic, thromboembolic, and opportunistic infection-related AEs in real-world settings. While expected toxicities (e.g., myelosuppression) were confirmed, novel signals like pulmonary embolism and neurotoxicity warrant further investigation. Clinicians should prioritize hematologic monitoring, thromboprophylaxis in high-risk patients, and *Pneumocystis* prophylaxis during corticosteroid co-administration. Future studies should validate these signals through prospective trials and mechanistic research to optimize TMZ’s risk-benefit profile in glioma therapy.